Feasibility of leaching poor ore in a pile - Vladimir Ivanovich Golik; Yuri Ivanovich Razorenov; Olga Germanovna Burdzieva (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
Relevance. Traditional beneficiation processes do not provide full disclosure of minerals due to the design parameters of the equipment, so they are modernized by attracting operations of hydrometallurgical and chemical processing, which increase the efficiency of enrichment due to application of a new kind of energy, for example, technology of chemical leaching of metals. The direction of increasing the volume of production of metals by leaching non-conforming raw materials and wastes of mining and processing in piles, which is used to produce copper, gold, uranium, becomes more relevant. The aim of the study is the proof of ecological-economic efficiency of leaching of non-conforming raw materials and wastes of mining and processing in a pile and substantiation of their prospects. Methods of the research include analysis and synthesis of results of previously performed theoretical and experimental studies and those borrowed from the literature, patent data in analysis modeling. Results. In the complex «hydrometallurgy and ore leaching» the least cost of the product is achieved when the uranium content in ore is 0,08 %. At increasing uranium content without growth in ore production output the rate of production decreases due to low recoveries of uranium and duration of leaching. Calculation of irrigation parameters is based on the laws of infiltration hydrodynamics and correlations between the solvent, its concentration and wetting zone diameter. Analytical modeling of leaching efficiency was implemented in designing low-grade ores processing in a specific field. The distinctive feature of the project is in cascade location of the equipment for gravity movement of the material. The processes are arranged according to the principle of maximum reduction of process pumping, trails of technological pipelines and other utilities. The practice of dumping leaching tailings contributes to development of waste natural leaching with migration of liquid chemical components in crust layers and gas ones - into atmosphere, that decreases uranium leaching rates in a pile, reducing it to the level of work in progress with the complexity of possibilities of deep disposal. Conclusions. After leaching in a pile, uranium content in leaching tailings remains high enough to be considered as poor ore with radiation impact on the environment. A promising direction for wasteless recovery of metals from sub-standard materials is a combination of chemical processing and mechanical activation in leaching.